The Sprouts of Post-Communist Revolution: Toward a Postmodern Lithuania? - Šaulauskas, Marius Povilas (Sociologija. Mintis ir veiksmas, 1998)
Nowadays we could hardly find a sociologist, who could reasonably deny the significance of the structural changes in the decade after the start of ‘singing revolution’ in Lithuania. The change occurred not only in the spheres of politics and economics; it slowly and reluctantly transformed the structure of the society, its values and norms. What is the logic of such change? Is it already possible to define the stages of post-communist development? Is it possible to delineate tendencies of the development? Whether Lithuania – together with other neighbors in the Eastern Europe – is capable of following the path of ‘post-modern’ democracy in the West; or, despite all the efforts, the paths of development are unprecedent.